The importance of the nurse in the materials and sterilization center: Guaranteing the safety and quality of processes (Research, Society and Development, 2023)
Objective: To analyze the importance of nurses in the Material and Sterilization Center (CME) to guarantee the safety and quality of the sterilization and reprocessing processes of hospital materials. Methods: Integrative review with method: bibliographical research of an exploratory descriptive nature. Results: 218 articles were found, 216 in Google Scholar, 02 in BVS and 02 in LILACS, which after reading the title and abstract found 50 articles, two in common in the LILACS and BVS databases with the necessary characteristics. Conclusion: There are several activities that integrate cleaning in the CME, in which deactivating team interaction and communication is the responsibility of the coordinating nurse and participating in these recommended processes. then, given the importance of protocols and clear information about what should be done. As a result, the nurse will ensure that all processes are followed, planned in the correct way to be carried out, works on the control of hospital infections together with the Hospital Infection Control Service (SCIH) promoting the improvement of workers and local work, The importance of his duties brings the desired security and reliable work in the processes he commands.